Pengawasan Pemeliharaan Insfrastruktur Di UPT PUPR Wilayah Manonjaya Kabupaten Tasikmalaya - Iim Ibrahim (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study used a qualitative descriptive method, data collection was carried out using instruments in the form of observation, interviews, documentation study and literature study. This is often done when the population is small, less than 30 people. The results showed that the supervision of infrastructure maintenance at UPT PUPR in the Manonjaya Region of Tasikmalaya Regency had been carried out well, although there were still a few obstacles due to the feeling of reluctance between leaders and employees where the supervision process had to be improved even better. The paya supervision is carried out in order to improve the infrastructure maintenance system, namely by the direct supervision method carried out at the place of the activity, for example conducting unannounced inspections and examinations. Furthermore, with indirect supervision, namely supervision carried out by conducting monitoring and reviewing of reports from the officials or work units concerned, functional supervisory apparatus, legislative supervision and community supervision.